A History of the Mind - Humphrey, Nicholas (London Vintage, 1993)
Takes the reader to the edges of current knowledge and back to the beginning of time, before "mind" existed, to construct a history of consciousness. Nicholas Humphrey's previous books include "Four
Includes Index
History
Keywords: Consciousness -- History. -- Mind and Body -- History. -- Senses and Sensation -- History